The Influence Of Work Environment, And Internal Communication On The Performance Of Employees Of The Supervision And Service Office Of Customs And Excise Type Madya Customs B Bandar Lampung - Antoni, Robet; Josiah , Trisnowati (Multidisciplinary Journals, 2025)
This study examines the influence of the work environment and internal communication on employee performance at the Office of Supervision and Customs Service Type Madya Pabean B Bandar Lampung, which plays a vital role in the country’s economy. While the office maintains satisfactory cleanliness and organization, issues such as inadequate ventilation, poor lighting, and limited break room facilities disrupt employee comfort and productivity. Additionally, ineffective internal communication, characterized by untimely information and a lack of interdepartmental collaboration, hinders performance. This research aims to identify these issues and develop strategies to enhance employee performance, ultimately optimizing the office's role in the national economy. This study aims to provide a systematic and accurate presentation of specific population facts through quantitative field research. Conducted at the Office of Supervision and Customs Service Type Madya Pabean B Bandar Lampung, this research investigates the effects of the Work Environment and Internal Communication on employee performance. Out of a total of 29 employees, 28 are used as a sample after excluding one from the population. The independent variables are Work Environment (X1) and Internal Communication (X2), while the dependent variable is Employee Performance (Y). The research will take place from May to June 2024 using a descriptive quantitative approach. The study concludes that the Work Environment significantly affects the performance of employees at the Office of Supervision and Customs Service Type Madya Pabean B Bandar Lampung, contributing 17.6%, thus confirming the first hypothesis. Internal Communication also has a significant impact on employee performance, contributing 11.3%, leading to the acceptance of the second hypothesis. Furthermore, both the Work Environment and Internal Communication together provide a significant influence on employee performance, with a total contribution of 58.0%, validating the third hypothesis.